Percepción del estudiante de la universidad nacional de Cajamarca con respecto a la actividad minera en el distrito de Cajamarca - Cueva Zavala, Miguel Angel (2019)
ABSTRACT The mining activity is one of the most profitable in the universal field and is one of the most income that provides the country, due to the diversity and quantity of minerals that the different regions of Peru possess; this characteristic has motivated national and international investors to see mining as an effective tool for development, thus generating new concessions that guarantee the benefit of their host communities with canon projects and promising royalties treatment. However, there is an element of vital importance in the exploitation of this profitable activity and it is the relationship with the community, which in our country is not the best, which in some way conditions its normal development and permanence within a region. For this reason it is necessary to know one of the many variables of this reality as is the perception of citizens, in this case the students of the main house of studies in the city of Cajamarca, since being the future professionals of the The city will play a role that is more than important in the stability of the mining activity of this city In this way the present investigation identified the perception of the students of the National University of Cajamarca with respect to the mining activity in the district of Cajamarca, where the perception regarding the economic, social and environmental impacts of the mining was evaluated; In the same way, we also sought to identify alternative activities that could be another development option in the city, according to the students' opinion. For the development of this research, the descriptive method was used, and the survey technique was used through a questionnaire of questions, which resulted in an interpretation of graphs where it was concluded that the perception has fairly even split positions; since half of the population considers the positive activity for the job that originated and the other half considers it negative given the unfulfilled commitments to date by the mining company operating in the district of the city of Cajamarca. On the other hand, students of the National University of Cajamarca, considers that tourism is an alternative activity that could also lead to the development of the region with fewer negative impacts than regret